Evaluation of repeated exposure systemic toxicity test of PVC with new plasticizer on rats via dual parenteral routes. Issue 1 (2nd January 2018) - Hou, Li; Fan, Chunguang; Liu, Chenghu; Qu, Qiujin; Wang, Chunren; Shi, Yanping
Abstract: Systemic toxicity caused by repeated exposure to both polar and nonpolar leachables of di(2-ethylhexyl)-1, 2-cyclohexane plasticized polyvinyl chloride (PVC) was evaluated with dual routes of parenteral administration method on rats in the study. Experimental group and control group were designed by researchers. Tail intravenous injection with 0.9% sodium chloride injection extracts and intraperitoneal injection with corn oil extracts were conducted to the experimental rats while tail intravenous injection with 0.9% sodium chloride Injection and intraperitoneal injection with corn oil were conducted to the control rats. After 14 days, blood specimens were collected for clinical pathology (hematology and clinical chemistry) analysis. Selected organs were weighed and a histopathological examination was conducted. As a result, compared with the control animals, there were no toxicity-related changes on the parameters above. The results show that the rats do not show obvious systemic toxicity reaction caused by repeated exposure with dual routes of parenteral administration method on rats after administration with both polar and nonpolar exacts of di(2-ethylhexyl)-1, 2-cyclohexane plasticized PVC simultaneously up for 14 days.